2015
DOI: 10.1016/j.snb.2015.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Self-heating effects in large arrangements of randomly oriented carbon nanofibers: Application to gas sensors

Abstract: a b s t r a c t Herein, we prove that self-heating effects occur in sensor films made of randomly oriented nanoparticles (electro-sprayed, drop-casted and paint-brushed films of carbon nanofibers). A 2-point calibration method, reliable enough to overcome the lack of reproducibility of low cost fabrication methods, is also proposed. Self-heating operation makes possible reaching temperatures up to 250 • C with power consumptions in the range of tens of mW. For certain low-temperature applications (<100 • C) ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 68 publications
4
50
0
Order By: Relevance
“…In both experiments, equivalent responses were obtained but their dynamics were clearly different. This fact may originate from differences in the local temperature achieved by each nanowire in self-heating mode, which leads to an overall response signal that averages the dynamics of nanowires operating at different temperatures [42].…”
Section: Application To Gas Sensingmentioning
confidence: 99%
“…In both experiments, equivalent responses were obtained but their dynamics were clearly different. This fact may originate from differences in the local temperature achieved by each nanowire in self-heating mode, which leads to an overall response signal that averages the dynamics of nanowires operating at different temperatures [42].…”
Section: Application To Gas Sensingmentioning
confidence: 99%
“…These arguments justified the need of individual nanostructures, and suggested that such effects were just unfeasible in large arrangements of nanowires 27 . However, as previously stated, recent experiments show that this is not the case: efficient self-heating can also be achieved in random arrangements of multiple 1D nanostructures 23,25 . This work aims to shed some light on the issue, identifying a broad, general cause for efficient self-heating in nanostructured systems.…”
Section: Introductionmentioning
confidence: 86%
“…That is the reason why this promising approach has just remained as an object of research, with limited applicability 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, to provide the activation energies necessary for the interaction of gas molecules with the oxide surface, since the gas adsorption or desorption on MOx is an endothermic processes 1 . Typically, thermal heating (in the range of 200-500 ˚C) or non-equilibrium processes (light illumination, UV or visible) are applied to provide the needed energies for surface activation 2,3 . Recently, we reported a promising concept to realize self-powered gas sensors that are capable of detecting gases at zero power.…”
mentioning
confidence: 99%